Analisis Kinerja Keuangan pada Perusahaan Jaringan Distribusi Ritel di Indonesia - Arief Fajar Aviyatno; Muammar Nur Kholid (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
Financial performance analysis plays a crucial role in assessing the overall health and effectiveness of a company. This research focuses on analyzing the financial performance of a retail distribution network company in Indonesia, utilizing quantitative descriptive methods. It employs financial ratio and common size analyses on primary data from financial statements to comprehend the company's financial position, profitability, liquidity, and solvency. Through a quantitative descriptive observational design, secondary data from literature and documents are collected. The analysis includes assessing liquidity via current and cash ratios, profitability through metrics like ROA, ROI, and ROE, as well as evaluating solvency using relevant ratios. The findings provide insights into the company's performance, revealing potential short-term issues due to decreasing current and cash ratios and fluctuations in profitability. These insights assist stakeholders in making informed decisions and formulating strategies, underscoring the significance of financial analysis in evaluating a company's health.